Perception and Attitude of Taxpayers Towards Digitalisation of Tax - Ms. Devika Agrawal (International Journal of Advanced Science and Technology, 2020)
Digitalisation has seeped into almost every area of our lives,how we make a living, executing mundane daily tasks to running major corporations, you name it. In simple terms, it has revolutionized how things are done. Trade and commerce have been revamped because while physical boundaries are present, the limitations they pose are non-existent. Digitalisation has given birth to countless new industries, which wouldn’t be possible even a century back. Present study has been undertaken about the tax system prevailing in our country, history of our tax system. Changes witnessed by the tax system from traditional way of filing returns of income from pen and paper method to digitalised way.This study will unfold the perception and attitude of common men during online filing of tax, how it has made their work easier, challenges faced by them for further simplification of procedure.